Problem-Based Learning and Civic Engagement in Undergraduate Education - Keegan, Louise C. and Losardo, Angela and McCullough, Kim C. (Communication Disorders Quarterly, 2017)
Problem-based learning and civic engagement are complementary constructivist andragogical approaches that emphasize active learning by guiding students to develop their own understanding and knowledge of a topic through experience and reflection. By providing examples of clinical cases and community-based experiences, these approaches can enhance and expand the sociocultural perceptions of the students, while also allowing them an opportunity to develop the valuable interprofessional skill of collaboration. This article introduces the reader to these two andragogical approaches, and argues that, when implemented concurrently, these approaches are ideal for undergraduate students completing communication sciences and disorders degrees. These teaching methods provide students with an opportunity to cultivate a professional identity, and by assuming responsibility for their own learning, begin to develop research and clinical skills.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xNTI1NzQwMTE2Njg1MTg0